2017
DOI: 10.1149/2.0021712jes
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Lithium Solid Electrolyte Interphase in Vinylene Carbonate Electrolytes Using Cu||LiFePO4Cells

Abstract: The influence of vinylene carbonate (VC) on the plating/stripping of lithium was investigated using Cu||LiFePO 4 cells. These cells allow for easy fabrication and in-situ generation of lithium, with no excess lithium to influence performance. Addition of VC to the electrolyte improves both capacity retention and efficiency. IR and XPS spectroscopy of the surface of the plated lithium suggests the presence of a significant amount of poly(VC) when the electrolyte (1.2 M LiPF 6 in ethylene carbonate (EC): ethyl m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…9 The C1s spectra contain peaks associated with CO 3 at 289.9 eV, C-O at 286.7 eV and C-C/C-H at 285.0 eV consistent with the generation of a combination of ROCO 2 Li and Li 2 CO 3 , as observed by IR spectroscopy. 11,13,18 The O1s spectrum contains a broad beak centered at ∼531.8 eV, consistent with a mixture of C-O and C=O containing species. 11,13,18 A peak for Li 2 O is also observed at 528 eV in the O1s spectrum.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…9 The C1s spectra contain peaks associated with CO 3 at 289.9 eV, C-O at 286.7 eV and C-C/C-H at 285.0 eV consistent with the generation of a combination of ROCO 2 Li and Li 2 CO 3 , as observed by IR spectroscopy. 11,13,18 The O1s spectrum contains a broad beak centered at ∼531.8 eV, consistent with a mixture of C-O and C=O containing species. 11,13,18 A peak for Li 2 O is also observed at 528 eV in the O1s spectrum.…”
Section: Resultsmentioning
confidence: 86%
“…11,13,18 The O1s spectrum contains a broad beak centered at ∼531.8 eV, consistent with a mixture of C-O and C=O containing species. 11,13,18 A peak for Li 2 O is also observed at 528 eV in the O1s spectrum. 11,13,18 Further, The F1s spectra are very similar, containing peaks at 685 eV and 687 eV consistent with LiF and Li x PF y O z , respectively.…”
Section: Resultsmentioning
confidence: 86%
“…The same group also reported that adding 5% vinylene carbonate (VC) to 1 m LiPF 6 in EC/EMC (3:7, vol) electrolyte led to a significant improvement in the capacity retention of Cu || LFP full cells (showing a LIRR of 95.1%). [ 52 ] The improvement was attributed to the formation of a polymeric SEI layer on the lithium surface.…”
Section: Strategies For Improving Performance Of Anode‐free Full Cellsmentioning
confidence: 99%
“…41 Repeated deposition and stripping in this manner presents the true reversibility of the electrolyte due to a fixed capacity of lithium in the cell. 71 In this work, AF cells with NMC-622 were used to test all electrolytes (Fig. 7c).…”
Section: Anodic Stability Of Ether-based Electrolytesmentioning
confidence: 99%